Can a mortality excess in remote areas of Australia be explained by Indigenous status? A case study using neonatal mortality in Queensland - Michael Coory (Elsevier, 2003)
Abstract Objective:To assess the extent to which Indigenous status confounds the association between remoteness and neonatal mortality in Queensland. Methods:We used routine data from the Queensland Perinatal Data Collection. Poisson regression modelling was used to assess confounding. Results:Babies born to Indigenous mothers have mortality rates 2.42 times those of the rest of the population, regardless of whether they live in urban, rural or remote areas (95% CI 2.09-2.80). The babies of non‐Indigenous women who live in remote areas have a low risk of neonatal death, similar to their rural and urban counterparts. Conclusion:In Queensland, the key demographic variable that determines neonatal mortality is Indigenous status, not remoteness. Implications:Policymakers should not assume that an excess of a particular health problem in remote areas necessarily reflects equal disadvantage for all the Australians who live there.